2014
DOI: 10.1097/jto.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Modulated Radiotherapy for Lung Cancer: Current Status and Future Developments

Abstract: Radiotherapy plays an important role in the management of lung cancer, with over 50% of patients receiving this modality at some point during their treatment. Intensity-modulated radiotherapy (IMRT) is a technique that adds fluence modulation to beam shaping, which improves radiotherapy dose conformity around the tumor and spares surrounding normal structures. Treatment with IMRT is becoming more widely available for the treatment of lung cancer, despite the paucity of high level evidence supporting the routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 79 publications
0
42
0
2
Order By: Relevance
“…Several studies have shown reduced toxicity for head and neck (4, 25) and breast cancer (26). For many clinical indications, superiority of IMRT has not been proven, or was proven only after IMRT was widely adopted (27). Also, the impact of an increase in the volume proximal to the tumor receiving a low radiation dose on the induction of secondary tumors has been insufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown reduced toxicity for head and neck (4, 25) and breast cancer (26). For many clinical indications, superiority of IMRT has not been proven, or was proven only after IMRT was widely adopted (27). Also, the impact of an increase in the volume proximal to the tumor receiving a low radiation dose on the induction of secondary tumors has been insufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, does VMAT with full Arc possibly increase toxicity compared with three-dimensional conformal radiation therapy? 42 Investigating this research question would be very meaningful. We are convinced, however, that a systematic collaboration between centres, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…3 This can be achieved through the use of advanced radiotherapy techniques. 84,85 Both the lung V20 (volume of lungs minus the planning target volume receiving 20 Gy) and the mean lung dose (volumes of lungs minus the gross tumor volume) correlate with the risk of radiation pneumonitis. 3 The V20 or the mean lung dose should be kept below 35%e37% and 20 Gy, respectively.…”
Section: Radiotherapy Techniques and Chemotherapy Adjustments To Prevmentioning
confidence: 99%